Simulation of Network Maneuvers at Power Substantions - Marwan, Marwan; Naim, Kurniawati; Qadarsih, Devi Nurfitiriani (Politeknik Negeri Ujung Pandang, 2021)
The purpose of this study is to simulate network maneuvers due to disruption in the distribution system. This research was conducted in the Daya substation from January to March 2019, transformer 20 MVA. To achieve the research goal, network maneuvers were carried out in accordance with the standard operation procedure (SOP) of PT. PLN by simulating the conditions before and after the maneuver under Digsilent. Based on the results of the study, it shows that there is a change in the loading value of several back-up feeders to cover consumers demand for day and night time.